EFISIENSI PENGGUNAAN MODAL KERJA PADA PT. DUTA ENERGI MANDIRI - Elfreda Aplonia Lau, rinaSITI ANNISA UMI PRIHATINI LCA. Robin Jonathan, (EKONOMIA, 2016)
Siti Annisa Umi Prihatini. 2014. Efficiency Working Capital At PT. Duta Energi Mandiri under the guidance of the father of LCA. Robin Jonathan as a supervisor I and mother Elfreda A. Lau as supervisor II.The problems in this study is whether the efficiency of working capital at PT. Duta Energi Mandiri in 2012 increased compared to 2011. The purpose of this study is to analyze the efficiency of working capital and working capital turnover PT. Duta Energi Mandiri in 2011 and 2012.Working capital turnover is a ratio showing the relationship between working capital to sales and show the number of sales that can be obtained for each rupiah working capital. While the efficiency of working capital management of working capital is held appropriately and required a careful planning and meticulous in order to really be used to finance the operations of the business as efficiently as possible for the sake of business development in order to produce the optimal profit. The hypothesis in this study is the decline in the efficiency of working capital at PT. Duta Energi Mandiri in 2012 compared to the period in 2011.The analytical tool used in this study is a cash turnover, accounts receivable turnover and inventory turnover, and turnover of working capital which compares net income with net working capital is current assets less current liabilities which will be known to the efficiency of working capital of the company.Based on the analysis, it appears that the cash turnover in 2011 amounted to 26.52 times greater than in 2012 reached 9.40. Turnover of receivables at PT. Duta Energi Mandiri in 2011 that is equal to 4.64 times greater than the accounts receivable turnover in 2012 is equal to 2.89 times. Inventory turnover at PT. Duta Energi Mandiri in 2011 was 184.6 times the decline in 2012 is equal to 80.5 times. Turnover of working capital in 2011 is larger by 5.38 times compared to the year 2012 amounted to 4.27 times, which means that by 2011 every US $ 1.00 of working capital could generate net sales of Rp 5.38.Based on the analysis, it can be seen that the efficiency of working capital at PT. Duta Energi Mandiri in 2011 is greater than the efficiency of working capital in 2012. Thus the hypothesis writer is a decline in the efficiency of working capital at PT. Duta Energi Mandiri in 2012 compared with the period in 2011 is unacceptable and unsubstantiated.